Polyethylene Terehthalate (PET) bottles waste as fine aggregate in concrete - Nadimalla, Altamashuddinkhan; Masjuki, Siti Aliyyah; Saad, Siti Asmahani; Ali, Maisarah (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
Concrete construction industry is one of the major sector utilizing natural resources to produce concrete for building constructions. The rapid increase in building constructions and the demand for natural aggregates has resulted in depletion natural resources at an alarming rate. Uncontrolled mining activity worsens the situation. Thus serious awareness has been taken into consideration, has to be identified as a potential river sand substitution for fine aggregates replacement in concrete. For this review, utilizing recycled material are described as a fine aggregate replacement to river sand, particularly recycled Polyethylene Terephthalate (PET) bottles. Recycled PET Bottles are categorized as nonbiodegradable waste materials which are injurious to health. Recycled PET bottles in concrete are economical and help in reducing disposal problems. Recycled PET bottles are pondered as the best eco-friendly alternative not only for resolving the problem of disposal but as a new construction material for concrete.